1982
DOI: 10.3171/jns.1982.57.3.0334
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin and cerebral vessel relaxation

Abstract: The authors have studied the ability of prostacyclin to reverse contractions of human basilar arteries in vitro that were induced by a wide range of substances implicated in the etiology of cerebral arterial spasm. Prostacyclin (10(-10) to 10(-6)M) caused a dose-related reversal of contractions induced by 5-hydroxytryptamine, noradrenaline, angiotensin II, prostaglandin (PG)F2 alpha, and U-46619 (a thromboxane-A2 mimetic). These agents were tested at concentrations or volumes that produced almost maximum or ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…In almost all studies of cerebral arteries, including those in humans, Ang II produced constriction (Edvinsson et al, 1979;Paul et al, 1982;Shimizu et al, 1986;Juul et al, 1987;Whalley et al, 1985;Naveri et al, 1994;Stenman and Edvinsson, 2004;Krueger and Cook, 1985;Toda et al, 1990;Toda and Hayashi, 1979). In the present study, we found that Ang II was a potent constrictor of the basilar artery in male mice.…”
Section: Effects Of Angiotensin II In the Cerebral Circulationmentioning
confidence: 99%
“…In almost all studies of cerebral arteries, including those in humans, Ang II produced constriction (Edvinsson et al, 1979;Paul et al, 1982;Shimizu et al, 1986;Juul et al, 1987;Whalley et al, 1985;Naveri et al, 1994;Stenman and Edvinsson, 2004;Krueger and Cook, 1985;Toda et al, 1990;Toda and Hayashi, 1979). In the present study, we found that Ang II was a potent constrictor of the basilar artery in male mice.…”
Section: Effects Of Angiotensin II In the Cerebral Circulationmentioning
confidence: 99%
“…8 Changes in 6-keto-PGF la biosynthesis and release have been studied only in experimental cerebral ischemia 12 ; the variation of its synthesis has been reported to be region-specific (in the hippocampus) and closely time-dependent (increased 30 minutes after reflow, and decreased to 60% of control at 24 hours). Prostacyclin is involved in regulation of the microcirculation, is synthesized by endothelial cells, has a marked vasodilating effect, 18 ' 38 and prevents blood-brain barrier derangement 39 and impairment due to postischemic brain reperfusion. 840 In our present study, the release of 6-keto-PGF, a was significantly reduced 1 and 6 hours after SAH; we hypothesize that at this time the endothelial damage caused by the SAH exerted an inhibitory effect on cyclooxygenase enzyme in the arterial wall.…”
mentioning
confidence: 99%
“…16,17 Prostacyclin in corresponding low concentrations has also been shown to improve vessel diameter in vitro. 7,8 Thus, a dose of 1 to 2 ng/kg per minute might be effective while the risk of the well-known dose-dependent adverse effects could be minimized. The low-dose prostacyclin used also fulfils the theoretical rationale for treatment by compensating for a reduced endogenous production which has been demonstrated in an animal SAH model.…”
Section: Prostacyclin Dose Rationalementioning
confidence: 99%
“…It is a potent vasodilator and inhibitor of leukocyte activation, platelet aggregation, and leukocyte-endothelial interactions, all of which are properties with a hypothetical impact on the development of DIND. 5 Animal studies and in vitro studies have demonstrated positive effects of prostacyclin on cerebral blood flow (CBF) and vasospasm, [6][7][8][9][10] and an imbalance in the prostacyclin-prostaglandin ratio has been proposed as a cause of vasospasm. 6,11 Although results from in vitro and animal studies are promising, few studies exist that investigate the possible effects of prostacyclin on cerebral…”
mentioning
confidence: 99%